2021
DOI: 10.3390/mi12080934
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of the Thermal Effect of Standing Surface Acoustic Waves in Microchannel by Fluoresence Intensity

Abstract: Temperature is an important parameter for many medical and biological applications. It is key to measuring the temperature of acoustofluidics devices for controlling the device’s temperature. In this paper, Rhodamine B was used to measure the temperature change of the microchannel induced by the SSAWs’ thermal effect in microfluidics. A thermocouple was integrated into the microfluidics device to calibrate the relationship between the fluorescent intensity ratios of Rhodamine B and the temperature. Then, the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…In a paper published in 2021, a tracer dye was used to measure the temperature change in a microchannel induced by the thermal effect of standing surface acoustic waves (SSAWs) in microfluidics. The results show that SSAWs can heat the immobile fluid rapidly to 80 • C and that the flow rates can influence the temperature of the liquid [14]. Furthermore, the temperature of the liquid in the microchannel rises as the input voltage increases [15].…”
Section: Introductionmentioning
confidence: 91%
“…In a paper published in 2021, a tracer dye was used to measure the temperature change in a microchannel induced by the thermal effect of standing surface acoustic waves (SSAWs) in microfluidics. The results show that SSAWs can heat the immobile fluid rapidly to 80 • C and that the flow rates can influence the temperature of the liquid [14]. Furthermore, the temperature of the liquid in the microchannel rises as the input voltage increases [15].…”
Section: Introductionmentioning
confidence: 91%
“…20,21 Although some recent works have indicated that under specific interdigital transducer (IDT) configurations (e.g., high excitation frequency, high input power, long excitation time, and near placement), the temperature within the microfluidic chamber can increase rapidly over a short period of time. 22,23 This can be completely avoided by preliminary device design and realtime regulation of the experimental parameters, 24 preventing irreversible damage to the treated biological samples from acoustic thermal effects. Therefore, acoustic tweezers could be a promising strategy for the applications of manipulation of microparticles and cells in clinical diagnosis, 25 dynamic cell assembly, 26 and oriented alignment of suspended bioparticles.…”
Section: Introductionmentioning
confidence: 99%
“…The miniaturization and integration of microfluidic devices could greatly reduce contamination and increase the efficiency of time, energy and material consumption, especially for many on-site working conditions outside a professional lab [8]. Temperature control is widely required in microfluidic systems that are designed for bioengineering analyses, forensic identifications, cryopreservation studies and chemical synthesis [9][10][11][12][13][14]. For example, PCR is a commonly used bioanalytical technique that amplifies a specific DNA segment from a few copies into several million copies within a few hours in vitro.…”
Section: Introductionmentioning
confidence: 99%